2000
DOI: 10.1345/aph.19341
|View full text |Cite
|
Sign up to set email alerts
|

Possible Serotonin Syndrome Associated with Buspirone Added to Fluoxetine

Abstract: Symptoms consistent with serotonin syndrome may develop with the concurrent administration of buspirone and fluoxetine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Although linezolid appeared to be effective in clinical trials and in numerous case reports for the treatment of various infections with gram-positive organisms [2][3][4][5][6], recent letters from prescribers and the manufacturer report that prolonged use of linezolid can lead to myelosuppression, including neutropenia, thrombocytopenia, and anemia [7]. According to a review by Kuter and Tillotson [7], many patients who developed severe myelosuppression in postmarketing surveillance were at increased risk for preexisting cytopenia or had decreased bone marrow reserve.…”
mentioning
confidence: 99%
“…Although linezolid appeared to be effective in clinical trials and in numerous case reports for the treatment of various infections with gram-positive organisms [2][3][4][5][6], recent letters from prescribers and the manufacturer report that prolonged use of linezolid can lead to myelosuppression, including neutropenia, thrombocytopenia, and anemia [7]. According to a review by Kuter and Tillotson [7], many patients who developed severe myelosuppression in postmarketing surveillance were at increased risk for preexisting cytopenia or had decreased bone marrow reserve.…”
mentioning
confidence: 99%
“…Several case studies have reported the development of serotonin toxicity by the combined use of SSRIs and 5-HT1A agonist anxiolytics;20,21 however, high body temperatures were not observed in these studies. The exacerbation of serotonin toxicity in the present cases by adding small doses of paroxetine while administering perospirone – acting both as a 5-HT1A receptor agonist and a 5-HT2A receptor antagonist – clearly indicates the involvement of the 5-HT1A receptor in mild forms of serotonin toxicity.…”
Section: Discussionmentioning
confidence: 81%
“…Recent case reports have suggested that there is a risk of the serotonin syndrome when SSRIs are combined with buspirone [36]. Recent case reports have suggested that there is a risk of the serotonin syndrome when SSRIs are combined with buspirone [36].…”
Section: Selective Serotonin Re-uptake Inhibitors (Ssris)mentioning
confidence: 99%